Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/ef9004708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biofuels on Nanoparticle Emissions from Spark- and Compression-ignited Single-cylinder Engines with Same Exhaust Displacement Volume

Abstract: Nanosized particles emitted from automotive engines continue to attract concern because of their adverse health effects and their impact on the environment. Automotive engines are a major source of fine and ultrafine particles emitted into the atmosphere. Through stricter emission regulations and the introduction of advanced technologies, the specific particulate mass emissions (in g/km and g/kWh) from internal combustion engines have decreased by about 1 order of magnitude since the 1980s. However, the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…26,27 When larger amounts of ethanol are added to the fuel mixture, ethanol pyrolysis prevails, leading to the formation of partially oxidized species, with the net effect of a reduction of the particle precursors and, lately, of the total mass of particulate matter. 4,28,29 It is worth noting that, also in the diffusioncontrolled conditions investigated at lab scale, the reducing effect of ethanol addition on the formation of the smaller size particles is overall less evident than the reduction of the total particulate matter. The concentration of the smaller size particles is not significantly reduced, and in some cases, it is even increased by the addition of ethanol.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…26,27 When larger amounts of ethanol are added to the fuel mixture, ethanol pyrolysis prevails, leading to the formation of partially oxidized species, with the net effect of a reduction of the particle precursors and, lately, of the total mass of particulate matter. 4,28,29 It is worth noting that, also in the diffusioncontrolled conditions investigated at lab scale, the reducing effect of ethanol addition on the formation of the smaller size particles is overall less evident than the reduction of the total particulate matter. The concentration of the smaller size particles is not significantly reduced, and in some cases, it is even increased by the addition of ethanol.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Small amounts of ethanol added to the fuel enhance the pyrolysis of the fuel mixture because of the presence of oxygen-containing radicals deriving from ethanol decomposition. The larger production of ethylene and methyl radicals allows for the molecular growth pathways that lead to the formation of aromatics and soot. , When larger amounts of ethanol are added to the fuel mixture, ethanol pyrolysis prevails, leading to the formation of partially oxidized species, with the net effect of a reduction of the particle precursors and, lately, of the total mass of particulate matter. ,, It is worth noting that, also in the diffusion-controlled conditions investigated at lab scale, the reducing effect of ethanol addition on the formation of the smaller size particles is overall less evident than the reduction of the total particulate matter. The concentration of the smaller size particles is not significantly reduced, and in some cases, it is even increased by the addition of ethanol .…”
Section: Introductionmentioning
confidence: 99%
“…In various research studies, ethanol blended fuels have shown reduced PM emissions in comparison to gasoline and its surrogate fuels [19][20][21] in DISI engines. However, there are also studies reporting increasing particulate concentration for gasoline engine fuels with higher ethanol content [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohols with longer carbon chain length have merit over shorter chain alcohols due to their higher calorific value, cetane number, improved miscibility with diesel, and superior cold flow properties [69,85]. The lower viscosity and density of alcohol blended fuels can improve the fuel atomization and fuel-air mixing consequently reducing the PM emissions [141][142][143]. A brief summary of observations made by different researchers for different alcohol fuels is presented in Table 2.…”
Section: Alcohol Fuelsmentioning
confidence: 99%